Comparative analysis of cow and buffalo milk based probiotic yoghurt formulations, for physicochemical, sensory, and in vitro biological activities - Muhammad Azhar Iqbal; Mian Anjum Murtaza; Aysha Sameen; Iram Hafiz; Ashiq Hussain; Tariq Aziz; Ashwag Shami; Nada K. Alharbi; Fahad Al-Asmari; Fakhria A. Al-Joufi (Food and Humanity, 2026)

Upregulation and diagnostic potential of Interleukin-36 cytokine isoforms in dilated cardiomyopathy: evidence from human and murine models - Alishba Kainat; Mubeen Tabish Nasim; Fazlul Aziz Mian; Syed Muhammad Nurulain; Hassaan Mehboob Awan; Tahir Iqbal; Sabir Hussain (Molecular Biology Reports, 2026)

Nano-formulated β-glucans from Saccharomyces cerevisiae enhance immunity and protection against coccidiosis in broiler chickens - Muhammad Noor; Muhammad Irfan Anwar; Mian Muhammad Awais; Masood Akhtar; Faqir Muhammad (Veterinary Parasitology, 2026)

Rational Ba doping induces multiphase architecture in PrNi0.5Co0.5O3-δ for enhanced triple conductivity in protonic ceramic electrochemical cells - Mengjun Tang; Xiao Zhang; Waqas Muhammad; Yinghua Niu; Sheng Ma; Zuorui Xin; Jiaqi Wang; Tingting Liu; Mian Li; Liping Dai; Jinquan Wang; Zihao Xu; et al. (Chemical Engineering Journal, 2026)

Maximizing weight loss with cagrisema: a systematic review and GRADE-assessed meta-analysis of randomized controlled trials - Bilal Wazir Khan; Syed AsadUllah Agha; Ihsan Qamar; Muhammad Huzaifa Khattak; Amna Rehman; Tayyaba Ikram Qazi; Shahreena Athar Siddiqui; Nafila Zeeshan; Umer Zaryab Khan; Humaira Bibi; Muhammad Faaz Khan; Haris Wazir Khan; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Green-Synthesized Zinc Oxide Nanoparticles from Selenicereus grandiflorus Exhibit Potent Nematicidal Activity Against Meloidogyne incognita - Sidra Ahmad; Mian Afaq Ahmad; Nayab Ahmad; Fazal Umer; Iqbal Munir; Md. Shahinoor Islam; Gulzar Ahmad; Muhammad Ijaz; Allah Ditta; Rashid Iqbal; Badr Aldahmash; Ahmed Rady (Current Microbiology, 2026)

Evaluation of Larvicidal Potential of Nepeta cataria and Cymbopogon nardus Essential Oils Against Aedes aegypti - Iqra Shafeeq; Sammina Mahmood; Adeel Sattar; Qamar Niaz; Mian Abdul Hafeez; Muhammad Ilyas; Muhammad Shahid Mahmood (Acta Parasitologica, 2026)

Elevated interleukin-36γ and gene polymorphisms implicate novel risk in essential hypertension - Alishba Kainat; Fazlul Aziz Mian; Muhammad Asif Nawaz Khan; Mubeen Tabish Nasim; Syed Muhammad Nurulain; Nazia Bibi; Syed Tahir Abbas Shah; Muhammad Jadoon Khan; Sabir Hussain (Immunogenetics, 2026)

Novel Hybrid Material as a Robust Photocatalyst for Degradation of Aqueous Phenolic Contamination - Bushra Bostan; Saima Sadiq; Inam Ullah; Makkah Zaman; Mian Muhammad; Muhammad Sadiq (Water, Air, & Soil Pollution, 2026)

Atg5-mediated autophagy modulation shapes the outcome of Bombyx mori Nucleopolyhedrovirus infection in silkworms - Nasir Mehmood; Mian Muhammad Awais; Wensheng Yu; Haixu Bian; Jingchen Sun (Journal of Invertebrate Pathology, 2026)

Retraction notice to “Assessment of hepatotoxicity and nephrotoxicity in Cirrhinus mrigala induced by trypan blue - an azo dye” [Environ. Res. 215 (2022) 114120] - Bilal Hussain; Muhammad Sajad; Hassan Usman; Khalid A. Al-Ghanim; Mian Nadeem Riaz; Aydin Berenjian; Shahid Mahboob; Pau Loke Show (Environmental Research, 2026)

Irradiation of hexaploid wheat (Triticum aestivum L.) seeds with varying doses of gamma radiation leads to novel mutants - Nasr Ullah Khan; Bareera Tu Nisa; Ihteram Ullah; Douglas Law; Daniel K. Y. Tan; Wael Elmenofy; Mian Abdur Rehman Arif; Muhammad Yasin (Cereal Research Communications, 2026)
The plateauing wheat yield and its narrow genetic diversity warrants modifying wheat to meet the global food demand from the growing population. Gamma radiation-based mutagenesis is a widely used technique to develop or improve crops like wheat. However, optimizing radiation dose level and the response of wheat genetic background to radiation dose are the two key challenges. This study was conducted to assess the effect of different gamma radiations doses (0 Gy, 100 Gy, 150 Gy, 200 Gy and 250 Gy) on early growth, development and yield related attributes of six wheat genotypes (AZRC Dera, RK2022, landrace-49, landrace-52, black wheat and Kashmiri landrace), and to screen out mutants with promising growth, developmental and yield related attributes. Eighteen different traits (early growth, phenology and yield of the wild type and M 1 mutants) of the six wheat genotypes revealed differences ( p < 0.01) among genotypes (wheat) and treatment (gamma radiation doses), underscoring the genetic diversity and differential radio-sensitivity of the wheat genotypes. Additionally, all the eighteen traits among all genotypes were negatively ( p < 0.01) affected at high dose of 250 Gy, while optimum dose of 150 Gy positively impacted early growth and yield related traits. Kashmiri landrace exhibited improved superior yield related attributes such as early maturity, longer spike, greater spikelets per spike, greater number of seeds per spike and superior seed weight per spike, making it an ideal genetic material for mutation breeding programs. Hierarchical clustering revealed five distinct clusters of genotypes, Kashmir landrace and black wheat being the most distinct genotypes. Gamma radiation mutagenesis produced a vast array of radio morphs such as double spikes per tiller, high tillering, dwarfing and altered spike architecture. These mutants provide novel and valuable genetic resources for wheat breeding.

A comprehensive review on nutritional, functional, and clinical perspectives of chia seeds and chia mucilage - Muhammad Arham Rauf; Maira Abdul Razzak; Fatima Waheed; Tabana Naz; Maham Fatima; Tanveer Ahmad; Muhammad Arslan; Usman Mir Khan; Mian Kamran Sharif (Bioactive Carbohydrates and Dietary Fibre, 2026)

The biological synthesis of iron oxide nanomaterials and their possible physiological and biochemical toxicities in Cyprinus carpio - Nadia Bibi; Nishita Narwal; Muhammad Anees; Huma Ayub; Mian Adnan Kakakhel; Tawaf Ali Shah; Ashraf Khalifa; Imran Ibrahim Shaikh (Ecotoxicology, 2026)

Advances in Internal Organogenesis: Differentiation and Morphogenesis of Human Ventral Cavity Organs - Muhammad Iqbal Qureshi; Afsar Ali Mian; Irfan Khan (Stem Cell Reviews and Reports, 2026)

Molecular Identification and Phylogenetic Analysis of Lumpy Skin Disease Virus-P32 Gene in Cattle of Potohar Region, Pakistan - Gohar Khadim; Aamer Ali Shah; Aayesha Riaz; Mian Muhammad Awais; Arfan Yousaf; Mahwish Ali; Bakhtawar Khadim; Nimra Riaz (Current Microbiology, 2026)

Level-crossing processing and deep convolutional neural network for arrhythmia classification in telehealth services - Syed Fawad Hussain; Saeed Mian Qaisar; Muhammad Sherjeel (Physical and Engineering Sciences in Medicine, 2026)

Financial technology and nuclear energy development: the moderating role of institutional quality in driving a sustainable future - Chuan Zhang; Mian Gohar Rahman Zafar; Muhammad Hafeez; Nie HongDi (Environment, Development and Sustainability, 2026)

PFAS-driven modulation of algal organic matter enhances dissolved organic matter reactivity and disinfection by-product formation: Mechanistic elucidation via multi-spectroscopic analysis, and mitigation by coagulation and nanofiltration - Mian Jawaduddin; Zhaoyang Su; Sajid Rashid; Muhammad Saboor Siddique; Nigel Graham; Wenzheng Yu (Journal of Hazardous Materials, 2026)

A Snapshot of Brucellosis as an Occupational Health Hazard in Animal Handlers of an Agroecological Zone of Southern Punjab, Pakistan - Abdul Sammad Ali Khan Shirwany; Mian Muhammad Awais; Saad Masood; Aayesha Riaz; Masood Akhtar; Hosny El-Adawy; Faqir Muhammad; Muhammad Irfan Anwar; Mamoona Chaudhry (Journal of Agromedicine, 2026)

Cidofovir induces antiviral immunity against Bombyx mori nucleopolyhedrovirus by modulating multiple immune pathways in silkworm - Nasir Mehmood; Mian Muhammad Awais; Guangyu Ma; Jian He; Ming Feng; Jingchen Sun (Pesticide Biochemistry and Physiology, 2026)

Investigating the Effect of Sn and Pt Doping and Co-doping on the Photocatalytic Efficiency of Zirconia for Degradation of Acid Yellow-76 - Mian Hussain Shah; Saima Sadiq; Umar Wahab; Inam Ullah; Sardar Hussain; Nasr Ullah; Safiullah Khan; Zaffar Iqbal; Muhammad Ismail; Aadil Nabi Chishti; Muhammad Sadiq (Water, Air, & Soil Pollution, 2025)

Variations in Wheat and Soil N Concentration by the Sole and Combined Foliar Application of NPK and Humic Acid Levels - Khadim Dawar; Shahid Ali; Ibad Ullah; Ishaq Ahmad Mian; Bushra Khan; Muhammad Tariq; Aamir Khan; Syed Sartaj Alam; Muhammad Mudasar Malik (Journal of Soil Science and Plant Nutrition, 2025)

Prevalence in Relation to Risk Factors of Babesia Bigemina in Bovines of Punjab (Pakistan) - Muhammad Wahab; Mian Abdul Hafeez; Faiza Aslam; Rimsha Farooq; Syeda Anam Sarwar; Waqas Ahmad; Liaqat Ali; Adeel Sattar; Waseem Khan (Acta Parasitologica, 2025)

Spectrophotometric Determination of Fluometuron Via Complexation with Fe(III): Method Development, Validation, and Application to Environmental Samples - Mian Muhammad; Mushtaq Ahmad; Sikandar Khan; Faiz Ali (Journal of Fluorescence, 2025)

A rapid screening method for detection of ampicillin residues in dairy milk - Nida Noreen; Bushra Akhtar; Chi-Chung Chou; Muhammad Irfan Anwar; Mian Muhammad Awais; Faqir Muhammad (Research in Veterinary Science, 2025)

Effect of Ocimum tenuiflorum L. compounds on Oreochromis mossambicus: a combination of molecular docking, biochemical dynamics, and antifertility assessment - Sajida Afzal; Siraj Khan; Muhammad Nauman Khan; Zahida Nasreen; Hansa Gul; Mian Inam Zaib; Hameed Alsamadany; Khalid H. Alamer; Ibtisam M. Alsudays; Muhammad Tahir Naseem (Aquaculture International, 2025)

Ultraviolet processing for mycotoxin mitigation: A sustainable approach to enhancing food safety and security - Abuzar; Hafiz Rizwan Sharif; Rizwan Arshad; Mian Kamran Sharif; Waqas Ashraf; Iahtisham Ul-Haq; Zafarullah Muhammad; Mohamed A. Fahmy; Sameh A. Korma; João M. Rocha (Toxicon, 2025)

Effects of bacteriophage supplementation on performance, gut health and blood biochemistry in broilers challenged with necrotic enteritis - Muhammad Muneeb; Ehsaan Ullah Khan; Saima; Muhammad Suleman; Mian Muhammad Awais; Sohail Ahmad (Research in Veterinary Science, 2025)

Epidemiology of Lumpy Skin Disease virus in large ruminants of Potohar region, Pakistan - Gohar Khadim; Aamer A. Shah; Aayesha Riaz; Arfan Yousaf; Mahwish Ali; Mian Muhammad Awais; Muhammad Arif Zafar; Bakhtawar Khadim; Nimra Riaz (Tropical Animal Health and Production, 2025)

Integrated landslide risk assessment utilizing open source satellite and ground data in the Himalayas of Northern Pakistan - Naseem Ahmad; Muhammad Shafique; Mian Luqman Hussain; Munawar Shah; Punyawi Jamjareegulgarn; Nassir Saad Alarifi; Mostafa R. Abukhadra (Natural Hazards, 2025)

Multivariate Statistical Evaluation of 20 Metals/Metalloid Levels in the Serum of Patients with Prostate Gland Diseases - Muhammad Abdul Qayyum; Mian H. R. Mahmood; Tahir Farooq; Ahmad Irfan; Shahid Iqbal; Nazim Hussain (Indian Journal of Clinical Biochemistry, 2025)

Correction: Ultrasensitive Fluorimetric Detection of Hg2+ Using a Thiourea-Based Chemosensor - Sikandar Khan; Mian Muhammad; Eid H. Alosaimi; Hamed M. Al-Saidi; Jari S. Algethami; Mohsen A. M. Alhamami (Journal of Fluorescence, 2025)

KPT-330, A New Candidate Drug for Targeting NOTCH1 Overexpression in T-cell Acute Lymphoblastic Leukemia, An In Vitro and Silico Study - Fariha Naz; Saima Ejaz; Tayyaba Wali; Atiqa Nudrat; Mian Abdur Rehaman Arif; Muhammad Qandeel Waheed; Fatma Hussain; Saadiya Zia (Cell Biochemistry and Biophysics, 2025)

Spatio-temporal analysis of PM2.5 and its association with elevation by using remote sensing: the scenario of Quetta, Pakistan - Laraib Ehtasham; Malik Muhammad Akhtar; Salman Tariq; Ishaq Ahmad Mian (Air Quality, Atmosphere & Health, 2025)

Status and prospects of omics in lentil: understanding mechanisms and impact on stress breeding under changing climate - Fawad Ali; Yiren Zhao; Arif Ali; Mian Abdur Rehman Arif; Obaid Ullah Shah; Muhammad Atif Azeem; Li Liao; Zhiyong Wang (Journal of Plant Biochemistry and Biotechnology, 2025)

Ultrasensitive Fluorimetric Detection of Hg2+ Using a Thiourea-Based Chemosensor - Sikandar Khan; Mian Muhammad; Eid H. Alosaimi; Hamed M. Al-Saidi; Jari S. Algethami; Mohsen A. M. Alhamami (Journal of Fluorescence, 2025)

Novel Thiourea-Based Chemosensor for Ultrasensitive and Selective Detection of Hg2+ - Mian Muhammad; Sikandar Khan; Hamed M. Al-Saidi; Jari S. Algethami; Mohsen A. M. Alhamami; Mubark Alshareef (Journal of Fluorescence, 2025)

UV-B Stress Regulates the Transcription of UVR8 Signal System-Related Gene and the Synthesis of Isoflavones in Soybean Sprouts - Guannan Liu; Yunyun Zhao; Mian Wang; Muhammad Bilal; Pei Wang; Chong Xie; Hansong Yu; Runqiang Yang (Journal of Plant Growth Regulation, 2025)

Investigating the impact of enzyme diversity in producing edible bird nest protein hydrolysates: Techno-functional, structural, molecular docking, and in vitro digestibility - Rabia Kanwal; Abdur Rehman; Muhammad Irfan; Mian Shamas Murtaza; Tabussam Tufail; Mian Anjum Murtaza; Tawfiq Alsulami; Ibrahim Khalifa; Song Miao (Food Structure, 2025)

Integrated debris flow hazard and risk assessment using UAV data and RAMMS, a case study in northern Pakistan - Naseem Ahmad; Muhammad Shafique; Mian Luqman Hussain; Israr Ullah (Natural Hazards, 2025)

Systematic review on buparvaquone resistance associated with non-synonymous mutation in drug binding genes site of Theileria annulate - Muhammad Rashid; Muhammad Hassan Hayat; Naveed Zahra; Mian Sayed Khan; Suleman; Muhammad Nadeem; Tauseef ur Rehman; Muhammad Ehsan; Muhammad Irfan Malik; Muhammad Kashif Obaid; Amir Bakhsh; Mohamed Aziz Darghouth; et al. (Veterinary Parasitology, 2024)

Assessment of natural radioactivity levels in rice samples and their implications for radiological protection - Hannan Younis; Mian Mateen Ullah; Muhammad Adil Khan; Farooq Ahmad; Umair Azeem; Muhammad Waseem; Khurram Mehboob; Muhammad Ajaz; Wazir Muhammad (Isotopes in Environmental and Health Studies, 2024)

Impact of different range areas on behavior, welfare, and performance of Naked Neck chickens - Saba Zahid; Muhammad Usman; Hafiz Muhammad Ishaq; Muhammad Faizan Haider; Mian Mubashar Saleem; Usman Elahi; Murrawat Hussain; Hafiz Rao Abdul Latif; Kinza Saleem; Sohail Ahmad; Tarek Amin Ebeid (Tropical Animal Health and Production, 2024)

Skipping irrigation at pre- and post-anthesis stages influences grain yield and starch contents of bread wheat derived from synthetic or landraces - Sajid Shokat; Mian Abdur Rehman Arif; Muhammad Qandeel Waheed; Fulai Liu; Carlos Guzmán; Sukhwinder Singh (Cereal Research Communications, 2024)
This study aims to evaluate the role of genetic diversity originated from three-way crosses of landraces and synthetic bread wheat derivatives attempted with elite cultivars to identify the genotypes having better grain yield as well as better starch contents under flowering stage drought stress. In total, 50 genotypes comprised of 47 derivatives of landraces and synthetics, and three standard varieties were grown in the fields of CIMMYT, Obregon following alpha lattice design with two replications. Drought stress was imposed by stopping the irrigation before anthesis and post-anthesis stages. Different traits related to physiological adaptations, earliness, grain yield and starch contents were decreased under drought stress except amylose which increased significantly. Canopy temperature depression was not significantly affected by drought stress. Further, we identified strong correlation of grain yield with plant height, normalized difference in vegetation index, plant maturity, spike length, grain number and thousand grain weight but negative with canopy temperature depression. Non-significant correlation of amylose and amylopectin was recorded with grain yield. Results revealed that genetic diversity derived from landraces and synthetic bread wheat can improve grain yield and starch contents but simultaneous improvement of both is elusive.

Purifying surface water contaminated with azo dyes using nanofiltration: Interactions between dyes and dissolved organic matter - Mian Jawaduddin; Zhaoyang Su; Muhammad Saboor Siddique; Sajid Rashid; Wenzheng Yu (Chemosphere, 2024)

Numerical investigation of vortex-induced vibrations (VIV) of a rotating cylinder in in-line and cross-flow directions subjected to oscillatory flow - Ubaid Ur Rehman; Adnan Munir; Niaz Bahadur Khan; Ming Zhao; Muhammad Kashif; Mohammad S. Islam; Zeeshan Saeed; Mian Ashfaq Ali (Ocean Engineering, 2024)

Distribution and bioaccumulation of trace elements in two Cyprinidae fish species in the Indus river, Pakistan, including the impact of hydraulic structure on macroinvertebrates' biodiversity - Muhammad Waseem Boota; Shan-e-hyder Soomro; Haoming Xia; Yaochen Qin; Mian Adnan Kakakhel; Chaode Yan; Luo Weiran; Jikun Xu (Environmental Research, 2024)

Assessing Asiatic black bear (Ursus thibetanus) temporal overlap and co-occurrence with sympatric species in the temperate zone of the Hindu Raj Mountain range - Faizan Ahmad; Muhammad Rehan; Eve Bohnett; Ammar Hassan; Sami Ullah; Shah Zeb; Hammad Ali Mian; Muhammad Kabir (European Journal of Wildlife Research, 2024)

Global Patterns of Agricultural Machine and Equipment Injuries- A Systematic Literature Review - Mian Muhammad Sajid Raza; Sihan Li; Salah F. Issa (Journal of Agromedicine, 2024)

Agricultural Injury Surveillance in the United States and Canada: A Systematic Literature Review - Sihan Li; Mian Muhammad Sajid Raza; Salah Issa (Journal of Agromedicine, 2024)

Genome-wide association study reveals novel genes on different chromosomal positions regulating boll weight in upland cotton (Gossypium hirsutum L.) - Zubair Iqbal; Muhammad Shahid Iqbal; Salman Alamery; Khurram Shehzad; Qamar U. Zaman; Safira Attacha; Zareen Sarfraz; Mian Faisal Nazir; Daowu Hu; Muhammad Mubashar Zafar; Aqib Zeb; Shoupuhe; et al. (Genetic Resources and Crop Evolution, 2024)

Alleviation of cadmium toxicity and fortification of zinc in wheat cultivars cultivated in Cd contaminated soil - Khadim Dawar; Ishaq Ahmad Mian; Shadman Khan; Anwar Zaman; Subhan Danish; Ke Liu; Matthew Tom Harrison; Shah Saud; Shah Hassan; Taufiq Nawaz; Imran Khan; Haitao Liu; et al. (South African Journal of Botany, 2023)

Evaluation of possible attenuative role of chrysoeriol against polyethylene microplastics instigated testicular damage: A biochemical, spermatogenic and histological study - Muhammad Umar Ijaz; Faria Saher; Nemra Aslam; Ali Hamza; Haseeb Anwar; Saad Alkahtani; Hammad Ahmad Khan; Mian Nadeem Riaz (Food and Chemical Toxicology, 2023)

Assessment of essential and toxic elemental concentrations in tumor and non-tumor tissues with risk of colorectal carcinoma in Pakistan - Muhammad Abdul Qayyum; Tahir Farooq; Aqsa Baig; Tanveer Hussain Bokhari; Muhammad Naveed Anjum; Mian Habib-ur-Rahman Mahmood; Ahmad Raza Ashraf; Khawaja Muddassir; Muhammad Ahmad (Journal of Trace Elements in Medicine and Biology, 2023)

Impregnation of biochar with montmorillonite and its activation for the removal of azithromycin from aqueous media - Muhammad Arif; Guijian Liu; Muhammad Zia ur Rehman; Md Manik Mian; Aniqa Ashraf; Balal Yousaf; Muhammad Saqib Rashid; Rafay Ahmed; Muhammad Imran; Mehr Ahmed Mujtaba Munir (Environmental Science and Pollution Research, 2023)

An ultrasensitive colorimetric and fluorescent “turn-on” chemosensor based on Schiff base for the detection of Cu2+ in the aqueous medium - Sikandar Khan; Mian Muhammad; Abdul Waheed Kamran; Hamed M. Al-Saidi; Salman S. Alharthi; Jari S. Algethami (Environmental Monitoring and Assessment, 2023)

Estimation of genetic diversity using seed storage protein (SSP) profiling in wild and cultivated species of Cicer L - Uswah Khalid; Muhammad Qandeel Waheed; Najma Parveen; Mian Abdur Rehman Arif; Anjuman Arif (Molecular Biology Reports, 2023)

Performance assessment of gridded climatic data and modeling spatial accuracy ranking matrix for gridded precipitation using a new pixel-based approach: a district-wise case study of Punjab - Muhammad Usman Saleem; Mian Sohail Akram (Arabian Journal of Geosciences, 2023)

A comprehensive review on phytochemistry, bioactivity and medicinal value of bioactive compounds of pomegranate (Punica granatum) - Muhammad Modassar Ali Nawaz Ranjha; Bakhtawar Shafique; Lufeng Wang; Shafeeqa Irfan; Muhammad Naeem Safdar; Mian Anjum Murtaza; Muhammad Nadeem; Shahid Mahmood; Ghulam Mueen-ud-Din; Hafiz Rehan Nadeem (Advances in Traditional Medicine, 2023)

Correction to: Morphology of testis, sperm, and spermatheca in two capable hybridized termite species indicates no interspecific reproductive isolation - Zahid Khan; Mian Sayed Khan; Suleman; Nehaz Muhammad; Haroon; Xiao-Hong Su; Lian-Xi Xing (International Journal of Tropical Insect Science, 2023)

Reduction of metronidazole in municipal wastewater and protection of activated sludge system using a novel immobilized Aspergillus tabacinus LZ-M - Xuan Yu; Chunlan Mao; Wenxue Wang; Saurabh Kulshrestha; Peng Zhang; Muhammad Usman; Simin Zong; Mian Gul Hilal; Yitian Fang; Huawen Han; Xiangkai Li (Bioresource Technology, 2023)

Highly selective and sensitive spectrofluorimetric method for determination of cypermethrin in different environmental samples - Mian Muhammad; Sikandar Khan; Gul Rahim; Walaa Alharbi; Khadijah H. Alharbi (Environmental Monitoring and Assessment, 2022)

Spatio-temporal landslide inventory and susceptibility assessment using Sentinel-2 in the Himalayan mountainous region of Pakistan - Alam Sher Bacha; Muhammad Shafique; Harald van der Werff; Mark van der Meijde; Mian Luqman Hussain; Sohail Wahid (Environmental Monitoring and Assessment, 2022)

Synthesis, Characterization and Applications of Schiff Base Chemosensor for Determination of Cr(III) Ions - Sikandar Khan; Mian Muhammad; Jari S. Algethami; Hamed M. Al-Saidi; Albandary Almahri; Athar Abdulfattah Hassanian (Journal of Fluorescence, 2022)

Spatial source apportionment of pollution and health risks in the agricultural soils of Shangla, Northern Pakistan: multistatistical approach - Shah Jehan; Seema Anjum Khattak; Sardar Khan; Lixin Wang; Liaqat Ali; Muhammad Waqas; Mian Luqman Hussain (Arabian Journal of Geosciences, 2022)

Morphology of testis, sperm, and spermatheca in two capable hybridized termite species indicates no interspecific reproductive isolation - Zahid Khan; Mian Sayed Khan; Suleman; Nehaz Muhammad; Haroon; Xiao-Hong Su; Lian-Xi Xing (International Journal of Tropical Insect Science, 2022)

Multivariate Investigation of Toxic and Essential Metals in the Serum from Various Types and Stages of Colorectal Cancer Patients - Mian H. R. Mahmood; Muhammad Abdul Qayyum; Farhan Yaseen; Tahir Farooq; Zahid Farooq; Muhammad Yaseen; Ahmad Irfan; Khawaja Muddassir; Muhammad Nadeem Zafar; Muhammad Tariq Qamar; Arshad Mehmood Abbasi; Hai-Yang Liu (Biological Trace Element Research, 2022)

Genetic basis of some physiological traits and yield in early and late sowing conditions in bread wheat (Triticum aestivum L.) - Mian Abdur Rehman Arif; Maryam Liaqat; Muhammad Imran; Muhammad Qandeel Waheed; Anjuman Arif; Sukhwinder Singh; Sajid Shokat (Journal of Applied Genetics, 2021)

Assessment of Hg accumulation in fish and scalp hair in fishing communities along river Swat, Pakistan - Muhammad Aamir Munir; Bushra Khan; Ishaq Ahmed Mian; Muhammad Rafiq; Samreen Shahzadi; Kashif Naeem; Iqbal Ahmad (Environmental Science and Pollution Research, 2021)

Charge-transfer complex–based spectrophotometric method for the determination of mesotrione in environmental samples - Mian Muhammad; Sikandar Khan; Hira Fayaz (Environmental Monitoring and Assessment, 2021)

Landslide assessment by using multi-temporal UAV datasets: a case study in northern Pakistan - Naseem Ahmad; Muhammad Shafique; Mian Luqman Hussain (Arabian Journal of Geosciences, 2021)

Biochar and leguminous cover crops as an alternative to summer fallowing for soil organic carbon and nutrient management in the wheat-maize-wheat cropping system under semiarid climate - Muhammad Arif; Ikramullah; Talha Jan; Muhammad Riaz; Kashif Akhtar; Salman Ali; Shahen Shah; Fazal Jalal; Ishaq A. Mian; Khadim Muhammad Dawar; Haiyan Wang (Journal of Soils and Sediments, 2021)

Landslide inventory and susceptibility assessment using multiple statistical approaches along the Karakoram highway, northern Pakistan - Mian Luqman Hussain; Muhammad Shafique; Alam Sher Bacha; Xiao-qing Chen; Hua-yong Chen (Journal of Mountain Science, 2021)

A Report on Molecular Detection and Phylogenetic Evaluation of Anaplasma marginale in Ticks and Blood Samples Collected from Cattle in District Layyah in Punjab (Pakistan) - Sehrish Ashraf; Asia Parveen; Mian Muhammad Awais; Quratulane Gillani; Munir Aktas; Sezayi Ozubek; Furhan Iqbal (Current Microbiology, 2021)

Microalgae Isolation for Nutrient Removal Assessment and Biodiesel Production - Muhammad Arif; Le Wang; El-Sayed Salama; Mian Sabir Hussain; Xiangkai Li; Mohammed Jalalah; M. S. Al-Assiri; Farid A. Harraz; Min-Kyu Ji; Pu Liu (BioEnergy Research, 2020)

Statistical Assessment of Toxic and Essential Metals in the Serum of Female Patients with Lung Carcinoma from Pakistan - Muhammad Abdul Qayyum; Zahid Farooq; Muhammad Yaseen; Mian HR Mahmood; Ahmad Irfan; Muhammad Nadeem Zafar; Muddassir Khawaja; Kashif Naeem; Dursun Kisa (Biological Trace Element Research, 2020)

Synthesis, characterization, and biocompatibility of lanthanum titanate nanoparticles in albino mice in a sex-specific manner - Irum Naz Akram; Sana Akhtar; Ghulam Khadija; Mian Muhammad Awais; Muhammad Latif; Aasia Noreen; Mehwish Mobeen; Fareeha Sajjad; Zahida Sardar; Shahid Iqbal; Muhammad Naeem Ashiq; Furhan Iqbal (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Microzonation map of the Abbottabad basin and immediate surroundings - Sarfraz Khan; Muhammad Waseem; Muhammad Asif Khan; Zahid Hussain; Waqas Ahmed; Ahmad Hamad Khaliq; Nisar Bin Umair; Mian Luqman Hussain (Journal of Seismology, 2020)

Human health risks by potentially toxic metals in drinking water along the Hattar Industrial Estate, Pakistan - Shah Jehan; Seema Anjum Khattak; Said Muhammad; Liaqat Ali; Abdur Rashid; Mian Luqman Hussain (Environmental Science and Pollution Research, 2020)

Coal mining trends, approaches, and safety hazards: a brief review - Muhammad Fahad Ullah; Abdullah M. Alamri; Khalid Mehmood; Mian Sohail Akram; Faisal Rehman; Saif Ur Rehman; Omar Riaz (Arabian Journal of Geosciences, 2018)

Geology as a proxy for Vs30-based seismic site characterization, a case study of northern Pakistan - Muhammad Shafique; Mian Luqman Hussain; M. Asif Khan; Mark van der Meijde; Sarfraz Khan (Arabian Journal of Geosciences, 2018)

Evaluation of immunostimulatory and immunotherapeutic effects of tropical mushroom (Lentinus edodes) against eimeriasis in chicken - Muhammad Irfan Ullah; Masood Akhtar; Mian Muhammad Awais; Muhammad Irfan Anwar; Kashfa Khaliq (Tropical Animal Health and Production, 2018)

Levels of Organotin Compounds in Selected Fish Species from the Arabian Gulf - Muhammad Waqar Ashraf; Abdus Salam; Atiq Mian (Bulletin of Environmental Contamination and Toxicology, 2017)

Low C/N ratio raw textile wastewater reduced labile C and enhanced organic-inorganic N and enzymatic activities in a semiarid alkaline soil - Mahnaz Roohi; Muhammad Riaz; Muhammad Saleem Arif; Sher Muhammad Shahzad; Tahira Yasmeen; Muhammad Arslan Ashraf; Muhammad Atif Riaz; Ishaq A. Mian (Environmental Science and Pollution Research, 2017)

Effect of oxytocin on serum biochemistry, liver enzymes, and metabolic hormones in lactating Nili Ravi buffaloes - Zafar Iqbal; Zia ur Rahman; Faqir Muhammad; Masood Akhtar; Mian Muhammad Awais; Tanweer Khaliq; Amar Nasir; Muhammad Nadeem; Kinza Khan; Hafiz Muhammad Arshad; Muhammad Abdul Basit (Tropical Animal Health and Production, 2015)

Cheddar Cheese Ripening and Flavor Characterization: A Review - Mian Anjum Murtaza; Salim Ur-Rehman; Faqir Muhammad Anjum; Nuzhat Huma; Iram Hafiz (Critical Reviews in Food Science and Nutrition, 2014)

Rice Bran: A Novel Functional Ingredient - Mian Kamran Sharif; Masood Sadiq Butt; Faqir Muhammad Anjum; Saima Hafiz Khan (Critical Reviews in Food Science and Nutrition, 2014)

Comparative study of alleviating effects of GSH, Se and Zn under combined contamination of cadmium and chromium in rice (Oryza sativa) - Fangbin Cao; Nanbo Wang; Mian Zhang; Huaxin Dai; Muhammad Dawood; Guoping Zhang; Feibo Wu (BioMetals, 2013)

Application and Opportunities of Pulses in Food System: A Review - Muhammad Asif; Lloyd W. Rooney; Rashida Ali; Mian N. Riaz (Critical Reviews in Food Science and Nutrition, 2013)

Seasonal prevalence of coccidiosis in industrial broiler chickens in Faisalabad, Punjab, Pakistan - Mian Muhammad Awais; Masood Akhtar; Zafar Iqbal; Faqir Muhammad; Muhammad Irfan Anwar (Tropical Animal Health and Production, 2012)

Stability of Vitamins during Extrusion - Mian N. Riaz; Muhammad Asif; Rashida Ali (Critical Reviews in Food Science and Nutrition, 2009)